Creative Thinking Skills of Junior High School Students in Solving Problems Based on Mathematics Anxiety - Stefany Margaretha Hutauruk; Dwi Juniati; Siti Khabibah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Creative thinking skills are essential 21st-century skills that students must master. One factor that can hinder the achievement of this skill is math anxiety. This study aims to describe students' creative thinking skills in relation to their level of math anxiety. The research method employed is a descriptive qualitative approach. This research was conducted at SMP Negeri 2 Ungaran with seventh-grade students as the research subjects. The research tools consisted of a mathematics anxiety questionnaire, a mathematics ability test, and interview guidelines. The data will be analyzed through the stages of reduction, presentation, and conclusion. The sampling technique used was purposive sampling, in which students with high and low levels of mathematics anxiety were selected. The research subjects selected were four students who had similar creative thinking abilities. The creative thinking process is characterized by fluency, flexibility, and novelty. Based on the research, students with low levels of math anxiety tend to be able to demonstrate fulfillment of creative thinking skill indicators. Meanwhile, students with high levels of math anxiety are not able to demonstrate fulfillment of creative thinking skill indicators. However, there are differences in the creative thinking process between students with high and low levels of math anxiety.